Geometric analysis of the MDF kerf-bending structure accuracy. Issue 2 (June 2022) - Lorenzoni, Barbara Ruschel; Silva, Fabio Pinto da
In digital design, rigid flat materials commonly hinder the fabrication of complex-curved geometries. A fabrication approach based on the socalled bending cut patterns or "kerf-bending" can be used to improve the ability of a material to bend. This bending method relies on a complex mechanical behavior, requiring an accurate evaluation of the resultant surface. By mastering the geometric effects, some adjustments can be made to the project so that the result better approximates the designer's intentions. This study focused on geometric accuracy of MDF kerfbending, including target-geometry design, cutting, bending, 3D scanning and analysis. It demonstrated that depending on the arc bending radius, the sample with a defined cut pattern may become excessively tensioned, protruding to the outside, or without enough stiffness to conform to an ideal shape. Experiments have validated this methodology and obtained a stable and precise half-cylinder by selecting the most adequate radius range for the material and parameters adopted.